Pengaruh Perceived Ease of Use dan Perceived Service Credibility terhadap Intention of Use Mobile Payment di Jakarta - Setiawan Setiawan (Universitas Tarumanagara, 2022)
The purpose of this research is to identify the effect of Perceived Ease of Use and Perceived Service Credibility on the Intention of Use mobile payment in Jakarta. The data in this research was collected through a questionnaire method using Google Form. The sample used as many as 324 respondents the owner of bank accounts and mobile payment application users who live in Jakarta. The research results showed that there is a positive and significant implication between Perceived Ease of Use and Perceived Service Credibility towards Intention of Use Mobile Payment in Jakarta. Tujuan dari riset ini adalah untuk mengidentifikasi pengaruh antara Perceived Ease of Use dan Perceived Service Credibility terhadap Intention of Use mobile payment di Jakarta. Data dalam penelitian ini diambil dari metode kuesioner menggunakan Google Form. Sampel yang digunakan sebanyak 324 orang responden pemilik rekening bank dan pengguna aplikasi mobile payment yang tinggal di Jakarta. Penelitian ini menggunakan teknik analisis PLS (Partial Least Square). Hasil penelitian ini menunjukan adanya pengaruh positif dan signifikan antara Perceived Ease of Use dan Perceived Service Credibility terhadap Intention of Use mobile payment di Jakarta.